Remote sensing assessment of available green water to increase crop production in seasonal floodplain wetlands of Sub-Saharan Africa - Ayyad, S.; Karimi, P.; Langensiepen, M.; Ribbe, L.; Rebelo, Lisa-Maria; Becker, M. (Elsevier, 2022)
Producing more food for a growing population requires sustainable crop intensification and diversification, particularly in high-potential areas such as the seasonal floodplain wetlands of sub-Saharan Africa (SSA). With emerging water shortages and concerns for conserving these multi-functional wetlands, a further expansion of the cropland area must be avoided as it would entail increased use of blue water for irrigation and infringe on valuable protected areas. We advocate an efficient use of the prevailing green water on the existing cropland areas, where small-scale farmers grow a single crop of rainfed lowland rice during the wet season. However, soil moisture at the onset of the rains (pre-rice niche) and residual soil moisture after rice harvest (post-rice niche) may suffice to cultivate short-cycled crops. We developed a methodological approach to analyze the potential for green water cultivation in the pre- and post-rice niches in the Kilombero Valley Floodplain in Tanzania, as a representative case for seasonal floodplain wetlands in SSA. The three-step approach used open-access remote sensing datasets to: (i) extract cropland areas; (ii) analyze soil moisture conditions using evaporative stress indices to identify the pre- and post-rice niches; and (iii) quantify the green water availability in the identified niches through actual evapotranspiration (AET). We identified distinct patterns of green water being available both before and after the rice-growing period. Based on the analyses of evaporative stress indices, the pre-rice niche tends to be longer (~70 days with average AET of 20–40 mm/10-day) but also more variable (inter-annual variability >30%) than the post-rice niche (~65 days with average AET of 10–30 mm/10-day, inter-annual variability <15%). These findings show the large potential for cultivating short-cycled crops beyond the rice-growing period, such as green manure, vegetables, maize, and forage legumes, by shifting a portion of the nonproductive AET flows (i.e., soil evaporation) to productive flows in form of crop transpiration. A cropland area of 1452 to 1637 km2 (53–60% of the total cropland area identified of 2730 km2) could be cultivated using available green water in the dry season, which shows the significance of such change for food security, livelihoods, and resilience of the agricultural community in Kilombero. A wider application of the developed approach in this study can help identifying opportunities and guiding interventions and investments towards establishing sustainable intensification and diversification practices in floodplain wetlands in SSA.